Một số trải nghiệm từ cách tiếp cận tầm nhìn ngôn ngữ Hồ Chí Minh... /Nguyễn Lai. - Nguyễn, Lai.
Language has both the comunicative and the perceptive functions. However, for Hochiminh, the ultimate goal of the comunicative and perceptivef functions is to stimulata the mass to stand up for a revolutionary action. This is why in studying Hochiminh s language, it is important to pay attention to his insghtful and revolutinary language vision which is the motivaton for hs language usages.